C57BL/6N mice show a sub-strain specific resistance to the psychotomimetic effects of ketamine - Harda, Zofia; Misiołek, Klaudia; Klimczak, Marta; Chrószcz, Magdalena; Rodriguez Parkitna, Jan (Frontiers in Behavioral Neuroscience, 2022)
Repeated administration of subanesthetic doses of ketamine is a model of psychosis-like state in rodents. In mice, this treatment produces a range of behavioral deficits, including impairment in social interactions and locomotion. To date, these phenotypes were described primarily in the Swiss and C3H/HeHsd mouse strains. A few studies investigated ketamine-induced behaviors in the C57BL/6J strain, but to our knowledge the C57BL/6N strain was not investigated thus far. This is surprising, as both C57BL/6 strains are widely used in behavioral and neuropsychopharmacological research, and are de facto standards for characterization of drug effects. The goal of this study was to determine if C57BL/6N mice are vulnerable to develop social deficits after five days withdrawal from sub-chronic ketamine treatment (5 days, 30 mg/kg, i.p.), an experimental schedule shown before to cause deficits in social interactions in C57BL/6J mice. Our results show that sub-chronic administration of ketamine that was reported to cause psychotic-like behavior in C57BL/6J mice does not induce appreciable behavioral alterations in C57BL/6N mice. Thus, we show that the effects of sub-chronic ketamine treatment in mice are sub-strain specific.